2010
DOI: 10.1016/j.chembiol.2010.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Defining Criteria for Oligomannose Immunogens for HIV Using Icosahedral Virus Capsid Scaffolds

Abstract: Summary The broadly neutralizing antibody 2G12 recognizes a conserved cluster of high mannose glycans on the surface envelope spike of HIV suggesting that the “glycan shield” defense of the virus can be breached and may, under the right circumstances, serve as a vaccine target. In an attempt to recreate features of the glycan shield semi-synthetically, oligomannosides were coupled to surface lysines on the icosahedral capsids of bacteriophage Qβ and cowpea mosaic virus (CPMV). The Qβ glycoconjugates, but not C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 70 publications
2
122
0
4
Order By: Relevance
“…In this approach, first and second generation glycodendrons have been prepared, which were conveniently functionalized for further conjugation on different scaffolds including a fullerene molecule or a virus-like particle protein. [32,33] …”
Section: Human Immunodeficiency Virus (Hiv) Representsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this approach, first and second generation glycodendrons have been prepared, which were conveniently functionalized for further conjugation on different scaffolds including a fullerene molecule or a virus-like particle protein. [32,33] …”
Section: Human Immunodeficiency Virus (Hiv) Representsmentioning
confidence: 99%
“…The inhibition data based on the number of carbohydrates radiuses showed that, in each case, the average affinity of a single glycoside of the fullerenes towards WaaC was significantly enhanced when it displayed as a multimer, thus demonstrating an multivalent effect. [21] Multivalent glycoconjugates are also used in anti adhesion leukacytotes to the endothelium for the prevention of inflammation.…”
Section: Glycodendrimers As Potential Therapeutic Agentsmentioning
confidence: 99%
“…Several recent studies have used viruses and virus-like particles as immunogenic scaffolds for a variety of molecules including glycans. [38][39][40][41] The requirements for viral self-assembly of rigidity and symmetry result in regular spacing of fixed, chemically accessible groups, thus making these platforms ideal for multivalent attachment of oligosaccharide determinants. Oligosaccharide cluster density is increasingly recognized as a major determinant for immunological discrimination between self and non-self CHO antigens.…”
Section: Filamentous Phage As a Carrier For Carbohydrate Haptensmentioning
confidence: 99%
“…Possible reasons for these failures include inadequate clustering of glycans, conformational flexibility induced by linker moieties and immunodominance of irrelevant CHO epitopes. 38 In collaboration with D. Bundle and J.J. Bailey (University of Alberta), we are pursuing an alternate strategy in which short chain oligosaccharides (mono-, di-, tetra-and/or pentamannose) will be attached to the filamentous phage pVIII via very short heterobifunctional linkers so as to minimize conformational flexibility (Fig. 5).…”
Section: Engineering Filamentous Phage As a Carriermentioning
confidence: 99%
See 1 more Smart Citation